Knowledge, attitude, and practice of breast self-examination is associated with general self-care and cultural factors: a study from Tamil Nadu, India - Bhoomika N. Jadhav; E.P. Abdul Azeez; Manoj Mathew; A.P. Senthil Kumar; M.R. Snegha; G. Yuvashree; S.N. Mangalagowri (BMC, 2024)
Abstract Aim Breast cancer is the most prevalent type of cancer among women. One form of care related to early detection of breast cancer is breast self-examination (BSE). However, evidence on knowledge, attitude, and practice (KAP) of BSE and its determining factors are minuscule in an Indian context. Therefore, the present study primarily examined the prevalence of KAP of BSE. Further, its association with general self-care and cultural factors was determined. Methods This cross-sectional study obtained data from 412 women (Mn age = 26.63) from two rural localities of Vellore district, Tamil Nadu, India. Self-reported questionnaires of KAP of BSE, self-care, and cultural factors were applied. Statistical analyses include independent sample t-test and binomial logistic regression. Results The majority of the sample had inadequate knowledge (58%), unfavourable attitudes (73.8%), and poor practice (89.6%) of BSE. The general self-care among the sample was moderate. Self-care was found to be a significant predictor of knowledge (b = 0.07, p < .05) and attitude (b = 0.092, p < .05) toward BSE. Shyness was identified as a negative predictor of KAP. Discouraged breast health discussions predicted inadequate knowledge, and not being educated by family/friends had a negative impact on knowledge and practice. A preference for same-gender physicians led to an unfavourable attitude toward BSE. Conclusion The observed negative trends in KAP of BSE are concerning. The results imply that girls and women should be educated and encouraged to practice BSE and promote self-care behaviours. At the same time, efforts to reduce cultural barriers may be helpful to promote the KAP of BSE.